Cooling temperature humidity index-days as a heat load indicator for milk production traits - Mbuthia, Jackson M.; Eggert, Anja; Reinsch, Norbert (Frontiers in Animal Science, 2022)
Well defined and accurate climatic indicators are important for evaluating heat stress in dairy cattle. This is imperative for sound management decisions for mitigating production losses. The most popular indicator for heat stress is the temperature humidity index (THI). Other heat stress indicators have been developed but remain largely unexploited. There is, therefore, possibly room to improve the THI and explore new indicators suitable for predicting production losses due to heat stress in dairy cattle. In this study we apply the degree-day concept to develop temperature humidity index-day (THI-day). We defined the cooling THI-day as the total hourly cumulative THI units that accumulated above the heat stress threshold for milk production traits over the entire day. We then modeled reaction norms for cooling THI-day to analyse the effect of cumulative heat load expressed by THI-day on milk production traits. Milk performance records were from 16,216,145 monthly test-day records for the Fleckvieh breed for the period 2010 to 2019 in southern Bavaria, Germanythe southern region of Bavaria Germany for the years 2010 to 2019. Individual cow records were averaged by herd and test-day resulting into 797,455 herd test-day records from 9,726 herds. Weather data for the same period were provided by the German Meteorological Service. Results indicated that cooling THI-day provided significant (p<0.001) additional information to the conventional THI models. We found out that reaction norm models of average herd milk yield that do not account for the cumulative heat load tend to underestimate the effects of heat stress on milk production traits. Reaction norms modeled with cooling THI-day were more plausible for milk production traits that have a defined heat stress threshold including milk yield, protein yield and milk urea.